Evaluación de la organización y funcionamiento de la dirección de posgrados de la universidad técnica de Cotopaxi frente al cumplimiento de los objetivos institucionales y propuesta de reforma alternativa - Guanín Tamayo, Marco Vinicio (2016)
This research work suggests evaluating the organization and operation of the unit Masters of UTC, towards the fulfillment of institutional objectives and alternative reform proposal, the purpose of this research is justify the need to implement an alternative reform, capable of providing the institution with a better organization and operation. Considering the institutional evaluation as the process of identifying and responding to the diverse interests and needs of all authorities, teachers and students through greater participation in the process of organization and operation. The theoretical basis that such research is supported responds to a different assessment concept to include all involved. It will cover changes and modifications in structures and strategies, with a common vision that includes all members of the institutional community and the community in which it develops, it is the responsibility of all those who are part of the educational community, with a commitment to provide better service and an active education, participatory discarding prejudices and stereotypes. This project will be feasible institutional development, in which two types of research will apply: field and documentary. The research population is the educational community, for that it will apply the technique survey, data collection and questionnaire as instrument. The resources will be use: human, technical, material and financial. The Community education beneficiaries of the Cotopaxi Technical University.